The joycean eros of Julián Ríos - Ferré, Juan Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Julián Ríos’s literature is the most creative and ingenious expression of the Joycean Eros in Spanish literature. The Joycean Eros is defined, in general lines, by its relationship with human language and the languages ​​of the world, in all its promiscuous plurality, as well as by its verbal staging of the realities and misunderstandings of sex and the equivocal comedy of the genres. From Larva: A Midsummer Night’s Babel (1983) to Puente de Alma (2009), Ríos’ narrative assumes that verbal and carnal heritage of Joyce, appropriates it without cultural complexes, incorporates it fully into his vast literary project, without losing an apex of uniqueness and originality, thus making one of the great postmodern contributions to a literature like that of Spain so devoid of those aesthetic, intellectual and cultural qualities.